2013
DOI: 10.1021/ed300438t
|View full text |Cite
|
Sign up to set email alerts
|

Using a Thematic Laboratory-Centered Curriculum To Teach General Chemistry

Abstract: This article describes an approach to general chemistry that involves teaching chemical concepts in the context of two thematic laboratory modules: environmental remediation and the fate of pharmaceuticals in the environment. These modules were designed based on active-learning pedagogies and involve multiple-week projects that dictate what content is taught and in which order the content is presented. Students were expected to design experimental procedures, analyze data, and communicate their results. A desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Project-based learning has been implemented both in the classroom and in the lab (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70) and can also be used to teach an entire course (71)(72)(73). In this case the laboratory and classroom experiences are combined into one activity (74).…”
Section: Project-based Learning As An Option For Facilitating Knowledmentioning
confidence: 99%
“…Project-based learning has been implemented both in the classroom and in the lab (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70) and can also be used to teach an entire course (71)(72)(73). In this case the laboratory and classroom experiences are combined into one activity (74).…”
Section: Project-based Learning As An Option For Facilitating Knowledmentioning
confidence: 99%
“…Moreover, students express dislike when lecture and laboratory are not well-aligned (Bieron et al, 1996), and concurrent enrollment in laboratory has been shown to improve retention and performance in introductory chemistry lectures (Matz et al, 2012). Because of these concerns about time, cost, and laboratory alignment with course learning objectives, instructional strategies in introductory chemistry courses have evolved to include emphasizing laboratory as the central component (Bopegedera, 2011;Hopkins and Samide, 2013), integration of laboratory components into lecture (Larsen et al, 2013), and a complete integration of laboratory with all other components of the course in what we refer to as a studio course.…”
Section: Introductionmentioning
confidence: 99%
“…T he challenge of getting engineering students of nonchemical majors engaged in introductory chemistry courses has been a subject of interest for a number of authors. 1−3 Various approaches are possible for the purpose of engaging students, including developing a theme surrounding the instruction process, 4 constructing an instrument for chemical applications, 5 and using social interaction and tactile technologies. 6 Fostering student interest is also accomplished through the laboratory experience, for example, by implementing inquirybased lab activities that promote social interaction 7 or even by creating dedicated rooms that simultaneously serve as classroom and laboratory space for semester-long projects.…”
mentioning
confidence: 99%
“…Various approaches are possible for the purpose of engaging students, including developing a theme surrounding the instruction process, constructing an instrument for chemical applications, and using social interaction and tactile technologies …”
mentioning
confidence: 99%